Konsep Tawakal Menurut Abdul Malik Karim Amrullah dan Relevansinya terhadap Kehidupan Sosial - Achmad Reza Hutama Al Faruqi; Rif'at Husnul Ma'afi; Rais Tandra Haibaiti (Program Studi Tasawuf dan Psikoterapi, 2022)
In the current era, there are so many people who feel that they are unlucky and even desperate with what they are currently facing, this trait arises because they do not understand the true nature of trust. Therefore, many people misinterpret the word tawakal. The article explains the concept of tawakal according to Abdul Malik Karim Amrullah and its relevance to social life, in the research process, the author collects data using library data with a Sufism approach and uses two methods, namely descriptive and analytical methods. From the results of the discussion, the researcher concluded that the concept of tawakal Abdul Malik Karim Amrullah agreed with other Sufi scholars, namely submitting decisions, all matters, endeavors, and efforts to God in the Universe, He is Strong and Powerful, we are weak and helpless. The difference between the concept and the concepts of other Sufi scholars is that tawakal must be accompanied by gratitude and patience in the face of His decrees. The relationship between the concept of tawakal Abdul Malik Karim Amrullah with social life is: making people strong and ready to face the problems of life.